2009
DOI: 10.1002/elps.200800720
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Western blots: Pitfalls of densitometry

Abstract: Although Western blots are frequently quantified, densitometry is not documented and appears to be based merely on traditions and guesswork. Confirming previous experience, none of 100 randomly selected and systematically scanned most recent papers provided sufficient information on how Western blot results were translated into statistical values. The importance of such information, however, becomes evident from our correlations of plasma erythropoietin values of various mammals determined using RIA and Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
266
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(278 citation statements)
references
References 14 publications
5
266
0
4
Order By: Relevance
“…ImageJ allowed us to measure the density profiles, peak heights, and peak intensity of the band of any expected molecular weight. Background correction was done using Rolling Ball Background Subtraction (rolling ball radius¼250; Gassmann et al, 2009). The contours of the rectangular boxes were determined arbitrarily using a width of approximately 30% of the lane and long enough to completely outline the bands of interest and the neighboring background.…”
Section: Western Blotsmentioning
confidence: 99%
“…ImageJ allowed us to measure the density profiles, peak heights, and peak intensity of the band of any expected molecular weight. Background correction was done using Rolling Ball Background Subtraction (rolling ball radius¼250; Gassmann et al, 2009). The contours of the rectangular boxes were determined arbitrarily using a width of approximately 30% of the lane and long enough to completely outline the bands of interest and the neighboring background.…”
Section: Western Blotsmentioning
confidence: 99%
“…Promising clones were then successively refined by two additional rounds of limiting dilution seeding and screening by Western blot. Quantification of Cul4B knockdown was performed using ImageJ (National Institutes of Health) as previously published (27). Nontarget control shRNA expressing RAW264.7 cells were maintained as a mixed population selected based on their resistance to 6 mg/ml puromycin.…”
Section: Immunoblottingmentioning
confidence: 99%
“…Image densitometry. Western blot quantification was meticulously performed using a procedure we developed based on the recommendations of Gassmann et al 38 Specifically, all quantified immunoblots were revealed using the same type of films (X-OMAT Blue XB, cat. 1776699, PerkinElmer, Waltham, MA, USA) and carefully exposed to avoid saturation.…”
Section: Discussionmentioning
confidence: 99%